2021
DOI: 10.1371/journal.pone.0260813
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microbiota of American Indian women and associations with measures of psychosocial stress

Abstract: Molecular-bacterial vaginosis (BV) is characterized by low levels of vaginal Lactobacillus species and is associated with higher risk of sexually transmitted infections (STI). Perceived psychosocial stress is associated with increased severity and persistence of infections, including STIs. American Indians have the highest rates of stress and high rates of STIs. The prevalence of molecular-BV among American Indian women is unknown. We sought to evaluate measures of psychosocial stress, such as historic loss (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 136 publications
(165 reference statements)
0
8
0
Order By: Relevance
“…Among the specimens used in this work, women with BV were more likely to be Black, have less education, and a current or past history of sexually transmitted infection (see Table S1). Although not examined here, other studies have found correlates between BV and psychosocial stress 81,82 . We cannot formally rule out contributions by potentially confounding factors to the glycan landscape.…”
Section: Discussionmentioning
confidence: 79%
“…Among the specimens used in this work, women with BV were more likely to be Black, have less education, and a current or past history of sexually transmitted infection (see Table S1). Although not examined here, other studies have found correlates between BV and psychosocial stress 81,82 . We cannot formally rule out contributions by potentially confounding factors to the glycan landscape.…”
Section: Discussionmentioning
confidence: 79%
“…In these experiments, samples were selected on the basis of BV status (Nugent 0 to 3 for negative and 7 to 10 for positive) from a larger cohort without introducing any strategies to balance the groups for potential confounders. Although not examined here, other studies have found correlates between BV and psychosocial stress (89,90). One limitation is that we cannot formally rule out contributions by potentially confounding factors to the glycan landscape.…”
Section: Discussionmentioning
confidence: 89%
“…Weathering may affect the vaginal microbiome as chronic stress doubles the risk of BV incidence. 60,61 African American women are exposed to higher levels of psychological and physiologic stressors compared with White women, 15,[62][63][64] including from perceived racial discrimination, poverty, poor housing, and exposure to crime. Social stressors are also associated with altered gut microbiota in mouse models.…”
Section: Psychosocial Stressors and Microbiome Dysbiosismentioning
confidence: 99%